Literature Review: Innovations in Biology Learning Media - GH, Muliana (EduLine: Journal of Education and Learning Innovation, 2024)
This research aims to identify the innovations in biology learning media that have been discovered and developed in the last 10 years. The research method used is a literature review method, utilizing secondary data from articles in national and international journals published between 2014 and 2024. Based on the research results, information was obtained regarding the biology learning media that have been used and developed over the past decade. These innovations in biology learning media include 32 types of innovations, consisting of 30 technology-based learning media and 2 non-technology learning media. The findings of this study are expected to serve as a reference for educators in using and developing biology learning media that align with the biology material or sub-topics.